Sister Mary Joseph's Nodule as a First Manifestation of Primary Peritoneal Cancer - C. Iavazzo; K. Madhuri; S. Essapen; N. Akrivos; A. Tailor; S. Butler-Manuel (Case Reports in Obstetrics and Gynecology)
Sister Mary Joseph's nodule metastasis is a rather rare finding. The primary malignancy in women is usually ovarian, endometrial, gastric, or pancreatobiliary tree cancer. We present a case of an 87-year-old patient with Sister Mary Joseph's nodule metastasis caused by a primary peritoneal malignancy. Through a literature search, we also discuss the pathophysiology, diagnostic approach, management, and prognosis of such a condition.